Methanotrophs Contribute to Nitrogen Fixation in Emergent Macrophytes - Cui, Jing; Zhang, Meng; Chen, Linxia; Zhang, Shaohua; Luo, Ying; Cao, Weiwei; Zhao, Ji; Wang, Lixin; Jia, Zhongjun; Bao, Zhihua (Frontiers in Microbiology, 2022)
Root-associated aerobic methanotroph plays an important role in reducing methane emissions from wetlands. In this study, we examined the activity of methane-dependent nitrogen fixation and active nitrogen-fixing bacterial communities on the roots of Typha angustifolia and Scirpus triqueter using a 15N-N2 feeding experiment and a cDNA-based clone library sequence of the nifH gene, respectively. A 15N-N2 feeding experiment showed that the N2 fixation rate of S. triqueter (1.74 μmol h−1 g−1 dry weight) was significantly higther than that of T. angustifolia (0.48 μmol h−1 g−1 dry weight). The presence of CH4 significantly increased the incorporation of 15N-labeled N2 into the roots of both plants, and the rate of CH4-dependent N2 fixation of S. triqueter (5.6 μmol h−1 g−1 dry weight) was 5-fold higher than that of T. angustifolia (0.94 μmol h−1 g−1 dry weight). The active root-associated diazotrophic communities differed between the plant species. Diazotrophic Methylosinus of the Methylocystaceae was dominant in S. triqueter, while Rhizobium of the Rhizobiaceae was dominant in T. angustifolia. However, there were no significant differences in the copy numbers of nifH between plant species. These results suggest that N2 fixation was enhanced by the oxidation of CH4 in the roots of macrophytes grown in natural wetlands and that root-associated Methylocystacea, including Methylosinus, contribute to CH4 oxidation-dependent N2 fixation.